Post-mortem 11.7 Tesla Magnetic Resonance Imaging vs. Polarized Light Imaging Microscopy to Measure the Angle and Orientation of Dorsal Root Afferents in the Human Cervical Dorsal Root Entry Zone - Henssen, Dylan Jozef Hendrik Augustinus; Weber, Rosanna Christina; de Boef, Jesse; Mollink, Jeroen; Kozicz, Tamas; Kurt, Erkan; van Cappellen van Walsum, Anne-Marie (Frontiers in Neuroanatomy, 2019)
Background: Destruction of the afferents by dorsal root entry zone (DREZ) surgery may be an effective treatment of intractable neuropathic pain, though it remains a high-risk surgical intervention. Potential complications due to the lesioning of structures within the cervical spinal cord other than the DREZ can be minimized by accurate knowledge of the optimal insertion angle [i.e., the angle between the DREZ and the posterior median sulcus (PMS)]. The employed insertion angle was based on measurements between the DREZ and the PMS on post-mortem transverse slices. However, new, more sophisticated imaging techniques are currently available and are thought to yield higher spatial resolution and more accurate images. Obejctive: This article measures the angle between the DREZ and the PMS on 11.7T post-mortem magnetic resonance images and compares these findings with polarized light imaging (PLI) microscopy images of the same specimens in order to quantify fiber orientation within the DREZ. Methods: To visualize the anatomy of the cervical DREZ, magnetic resonance imaging (MRI), diffusion-weighted MRI (dMRI), probabilistic tractography, and PLI were performed on three post-mortem human cervical spinal cords at level C5–C6. The MR data was used to measure the angle between the DREZ and the PMS. MR images were complemented by probabilistic tractography results. Then, the orientation of fibers within the DREZ was quantified by use of PLI microscopy. Results: Median angle between the DREZ and the PMS, as measured on MR-images, was found to be 40.1° (ranging from 34.2° to 49.1°) and 39.8° (ranging from 31.1° to 47.8°) in the left and right hemicord, respectively. Median fiber orientation within the DREZ, as quantified by PLI, was 28.5° (ranging from 12.0° to 44.3°) and 27.7° (ranging from 8.5° to 38.1°) in the left and right hemicord, respectively. Conclusion: Our study, which provides an improved understanding of the anatomy of the DREZ, the angle between the DREZ and the PMS and the median fiber orientation within the DREZ, could contribute to safer DREZ-lesioning surgery to treat chronic neuropathic pain in the future.